2008
DOI: 10.1177/1046878107310609
|View full text |Cite
|
Sign up to set email alerts
|

How a deaf boy gamed his way to second-language acquisition: Tales of intersubjectivity

Abstract: Taking an experiential approach to language development, this article links gaming to the language development of a 10-year-old deaf child under speech therapy. Specifically, it examines face-to-face interactions between mediators and the child, during 1 year of gaming in clinical encounters. To do so, it codes data by means of interactional variables (intentionality and subjectivity/intersubjectivity) and textual variables (function versus content words). Results show that gaming yielded affordances in the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In this review, we found one intervention that explicitly focused on this kind of optimisation: the DIM/Contact Program (Janssen et al, 2003). Although the effects of the video-feedback intervention on more elaborate ways of meaning-making are as yet unclear, studies that concern the development of tertiary intersubjectivity in children with deafness (Loots et al, 2005;Saliés & Starosky, 2008;Swanwick & Watson, 2007) and blindness (Junefelt, 2004;Wilson & Peters, 1988) suggest that other partner strategies need to be added to mediate the development of joint attention and the use of referential and symbolic communication. This intervention might also help to establish sustained dyadic interaction between children with deafness and their hearing partners, paving the way for sharing different kinds of meanings in conversations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this review, we found one intervention that explicitly focused on this kind of optimisation: the DIM/Contact Program (Janssen et al, 2003). Although the effects of the video-feedback intervention on more elaborate ways of meaning-making are as yet unclear, studies that concern the development of tertiary intersubjectivity in children with deafness (Loots et al, 2005;Saliés & Starosky, 2008;Swanwick & Watson, 2007) and blindness (Junefelt, 2004;Wilson & Peters, 1988) suggest that other partner strategies need to be added to mediate the development of joint attention and the use of referential and symbolic communication. This intervention might also help to establish sustained dyadic interaction between children with deafness and their hearing partners, paving the way for sharing different kinds of meanings in conversations.…”
Section: Discussionmentioning
confidence: 99%
“…The term "intersubjectivity" was not used for the study variables in most of these studies (except for Loots, Devisé, & Jacquet, 2005;Saliés & Starosky, 2008). Although other authors did not explicitly measure "intersubjectivity", they measured variables that could be attributed to one of the layers of intersubjectivity that Trevarthen described.…”
Section: Intersubjectivity Measuresmentioning
confidence: 99%
See 3 more Smart Citations